Rare earth sulfide energy-saving material and preparation method thereof
By preparing the rare earth sulfide composite material Ln2S3@A:xB:C, the problems of complex processes and poor thermal stability of existing energy-saving materials are solved, and the temperature regulation and energy-saving effect are achieved throughout the weather and energy-saving effect are improved, and the weather resistance and thermal conductivity of the materials are improved.
Patent Information
- Application Number
- CN202510510828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-07-25
AI Technical Summary
The existing energy-saving materials have complex processes and poor thermal stability performance, which cannot effectively regulate temperatures all-weather, resulting in energy waste and environmental pollution.
The preparation method of rare earth sulfide composite material Ln2S3@A:xB:C is adopted. Through the combination of core-shell material A, functional temperature-regulating material B and loading material C, high temperature absorption and low temperature release latent heat, achieving all-weather energy-saving effect, and structural stability is enhanced through loading material C.
It realizes all-weather temperature regulation capability, significantly improves energy-saving performance and thermal stability, especially at night, the latent heat effect through phase change is significant, and the weather resistance and thermal conductivity of the material is enhanced.
Smart Images

Figure CN120365895A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy-saving materials, and particularly to a rare earth sulfide energy-saving material and a preparation method thereof. Technical Background
[0002] Energy-saving materials refer to materials that can reduce energy consumption and maintain the ambient temperature. Their main function is to prevent the transfer and mutual influence of heat, cold air, and moisture in the fields of construction, industry, transportation, etc., so as to achieve the purpose of saving energy, improving production efficiency, and improving the living environment. Energy-saving materials are widely used in the construction field. For example, in buildings, energy-saving materials can store the heat absorbed during the day and release the heat through phase change at night, with significant energy-saving effects, thereby improving the stability of indoor temperature and reducing the energy consumption of heating and air conditioning, achieving the purpose of energy conservation and emission reduction.
[0003] With the development of the economy, more and more countries have realized the importance of climate change, because the quality of the environment is directly related to the survival and development of mankind. Since energy-saving materials can reduce energy consumption, thereby effectively reducing the emission and release of chemical substances and harmful substances and reducing environmental pollution, energy-saving materials have been widely developed. However, the current energy-saving materials generally have the problems of complex processes and poor thermal stability. Summary of the Invention
[0004] The purpose of the present invention is to provide a rare earth sulfide energy-saving material and a preparation method thereof to solve the problems raised in the above background technology.
[0005] To achieve the above purpose, the present invention provides the following technical solutions:
[0006] A rare earth sulfide energy-saving material is prepared from a core-shell material A, a functional temperature-regulating material B, a loading material C, and rare earth sulfide Ln2S3, and its chemical composition is Ln2S3@A:xB:C, where x represents the mass fraction of B, which is any value between 0.1 and 0.3 relative to the mass ratio of the energy-saving material. Ln2S3 is obtained by solid-phase sintering after grinding and mixing a flux, a sulfur source, and a rare earth-based sulfurization precursor according to a ratio.
[0007] As a further scheme of the present invention: the core-shell material A is titanium oxide doped with tungsten or vanadium dioxide.
[0008] As a further scheme of the present invention: the functional temperature-regulating material B is one or more of hexadecane, heptadecane, octadecane, glycerol, octanoic acid, and decanoic acid.
[0009] As a further scheme of the present invention: the loading material C is one or more of polypropylene, polystyrene, polyurethane, polymethyl methacrylate, polycarbonate, and polyvinylidene fluoride-hexafluoropropylene.
[0010] As a further embodiment of the present invention: the rare earth-based sulfurization precursor is a mixture of Ln compound and doping element compound, and the molar ratio of Ln to the doping element is (1 - 0.95):(0 - 0.05), where Ln is one of lanthanum, yttrium, samarium, neodymium, cerium, and europium, and the doping element is one of gallium, zinc, aluminum, sodium, barium, and tin.
[0011] As a further embodiment of the present invention: the flux is one or more of sodium carbonate, sodium chloride, and sodium sulfate.
[0012] As a further embodiment of the present invention: the sulfur source is one or more of sulfur powder, ammonium thiocyanate, and thiourea.
[0013] A preparation method of a rare earth sulfide composite energy-saving material, comprising the following steps:
[0014] S1. Take out the flux, sulfur source, and rare earth-based sulfurization precursor according to the molar ratio of (2 - 4):(45 - 60):(90 - 110), grind and mix them, and then perform solid-phase sintering to obtain a first product for standby;
[0015] S2. Take out the metal precursor and tungsten oxide precursor solution according to the molar ratio of (99 - 20):(1), dissolve the metal precursor in an ethanol solvent, stir and add it to the tungsten oxide precursor solution, adjust the pH to 3 - 5 to form a sol, and obtain core-shell material A after calcination;
[0016] S3. Take out the first product and surfactant according to the ratio of (2 - 4g):(0.01 - 0.1g), dissolve them in ethanol and stir, adjust the pH, and then slowly add core-shell material A. Wash and dry the product to obtain a second product for standby;
[0017] S4. Take out the second product, dispersant, functional temperature-regulating material B, and load C according to the mass ratio of (0.3 - 5):1:(5 - 7):(5 - 9), dissolve them in water and ultrasonically mix to form a homogeneous solution. Slowly introduce the homogeneous solution into a petri dish and perform a leveling operation, and then naturally dry it at room temperature to obtain the rare earth sulfide composite energy-saving material Ln2S3@A:xB:C.
[0018] As a further embodiment of the present invention: in the S1 step, the sintering furnace is one of a box furnace, a tube furnace, and a lifting furnace, the sintering temperature is 800 - 1000 °C, the sintering time is 1 - 8 h, and the sintering atmosphere is an air atmosphere.
[0019] As a further solution of the present invention: in the S1 step, the grinding and mixing is one of ball milling, air milling and water milling; wherein the ball milling rate is 80-900 r / min, and the ball milling time is 1-4 h; the air milling rate is 70-800 r / min, and the ball milling time is 1-4 h; the water milling rate is 80-950 r / min, and the water milling time is 1-4 h.
[0020] As a further solution of the present invention: in the step S2, the stirring rate is 300-600 r / min, and the stirring time is 3-6 h.
[0021] As a further solution of the present invention: in the step S3, the surfactant is one of polyvinyl pyrrolidone, polyoxyethylene ether, polyethylene glycol, and alkylphenol polyoxyethylene ether.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention adjusts the temperature by adding a functional temperature regulating material B, which absorbs heat at high temperature and releases latent heat at low temperature, thereby achieving an all-weather energy-saving effect, especially at night when the latent heat of phase change is significantly utilized, and has good thermal stability and weather resistance and excellent energy-saving performance; the liquid phase flow generated during the phase change process of the functional temperature regulating material will affect the stability of the structure, and the load material C plays a role in enhancing the thermal conductivity and structural stability of the functional material B. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a SEM image of La2S3 in Example 2 of the present invention;
[0025] Figure 2 The La2S3@Ti in Example 3 of the present invention 0.99 W 0.01 O2:0.2C 17 H 36 : SEM image of P(VDF-HFP);
[0026] Figure 3 is La2S3@V in Example 3 of the present invention 0.99 W 0.01 O2:0.2C 16 H 34 : Outdoor temperature rise curves of P(VDF-HFP) coated and uncoated wood cubes;
[0027] Figure 4 is Na in Example 5 of the present invention 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3: Temperature curves of PC coated and uncoated acrylic blocks under high temperature environment;
[0028] Figure 5 For Ba in Embodiment 6 of the present invention 0.012 Sm 1.988 S3@Ti 0.95 W 0.05 Temperature curve graphs of coated and uncoated acrylic blocks with O2:0.2CH3(CH2)6COOH:PP at low temperature environments;
[0029] Figure 6 For Sn in Embodiment 7 of the present invention 0.02 Eu 1.98 S3@V 0.99 W 0.01 Diffuse reflection diagram of O2:0.2CH3(CH2)8COOH:P(VDF-HFP). Detailed implementation manners
[0030] Embodiment 1
[0031] In the embodiments of the present invention, a rare earth sulfide energy-saving material with a chemical composition of Ln2S3@A:xB:C is Ga 0.03 Ce 1.98 S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :PMMA; The preparation method is as follows:
[0032] S1. According to the molar ratio of each element in Ga 0.03 Ce 1.98 S3, accurately weigh gallium oxide, cerium carbonate, and sulfur, and after grinding and mixing the three, perform solid-phase sintering to obtain a first product for standby;
[0033] S2. Take tetrabutyl titanate and ammonium tungstate solutions according to a molar ratio of 99:0.143. Dissolve tetrabutyl titanate in an ethanol solvent, stir and add it to the ammonium tungstate solution and 1 wt% polyvinyl alcohol, adjust the pH to 3-5 to form a sol, and obtain a core-shell material A after calcination;
[0034] S3. Take the first product, ammonia water, and alkylphenol polyoxyethylene ether according to a ratio of (2-4 g):(2-4 ml):(0.01-0.1 g), dissolve them in ethanol, stir, and slowly add the core-shell material A. Wash and dry the product to obtain a second product for standby;
[0035] S4. Take the second product, acetone, C 17 H 36After [substance] and PMMA are dissolved in water and ultrasonically mixed into a homogeneous solution, the homogeneous solution is slowly introduced into a petri dish and leveled, and then naturally dried at room temperature to obtain the rare earth sulfide energy-saving material Ga 0.03 Ce 1.98 S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :PMMA.
[0036] Apply Ga 0.03 Ce 1.98 S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :PMMA on the surface of a 20*20*20 cm cube made of wood. At the same time, an uncoated sample is selected as a comparison. The two groups of samples are placed at room temperature from 9:00 am to 3:00 pm. By comparing with the uncoated sample, it is found that the internal temperature of the wood coated with Ga 0.03 Ce 1.98 S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :PMMA has decreased by 6°C. The internal temperature of the wood is measured at night from 18:00 to 5:00 the next day. By comparison, it is found that the internal temperature of the wood coated with Ga 0.03 Ce 1.98 S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :PMMA has increased by 4.8°C. Its weather resistance level is detected to be 5, the salt spray resistance time is 2000 h, and the light resistance level is 8.
[0037] Example 2
[0038] In the embodiment of the present invention, a rare earth sulfide energy-saving material with a chemical composition of Ln2S3@A:xB:C is La2S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :P(VDF-HFP); its preparation method is as follows:
[0039] S1. According to the molar ratio of each element in the chemical formula La2S3, accurately weigh lanthanum carbonate and sulfur and put them into a jar mill. Set the rotation speed to 1000 r / min and grind for 2 h to obtain a first mixture for standby;
[0040] S2. After taking out sulfur according to the molar ratio of 2:1, put the sulfur into a pot mill, set the rotation speed at 1000 r / min, grind it for 2 h by air milling, then add activated carbon particles to obtain a second mixture for standby;
[0041] S3. After taking out the first mixture and the second mixture according to the mass ratio of 1.25:1, wrap the first mixture in the second mixture in a cylindrical crucible and put it into a sintering furnace. Sinter it at 950 °C for 3 h in an air atmosphere. After cooling to room temperature, take it out, remove the wrapping layer, and then grind the sintered product to obtain La2S3; the thermal stability of the measured La2S3 is 400 °C, the diffuse reflection in its infrared light band reaches 86%, and the yellowness value reaches 68.00; the SEM diagram of La2S3 is as Figure 2 shown, it can be seen from Figure 2 that the La2S3 particles show an aggregation situation;
[0042] S4. Take out tetrabutyl titanate and ammonium tungstate solution according to the molar ratio of 99:0.143, dissolve tetrabutyl titanate in an ethanol solvent, stir and add ammonium tungstate solution and 1 wt% polyvinyl alcohol, adjust the pH to 3 - 5 to form a sol, and obtain core-shell material A after calcination;
[0043] S5. Take out La2S3, polyvinylpyrrolidone and ammonia water according to the mass ratio of 2:0.02:2, add an appropriate amount of ethanol, set the rotation speed at 500 r / min and stir for 3 h, and add core-shell material A. Wash and dry the obtained product to get La2S3@Ti 0.99 W 0.01 O2 for standby;
[0044] S6. Mix La2S3@Ti 0.99 W 0.01 O2 with P(VDF-HFP), acetone, C 17 H 36 and water according to the molar ratio of 2:1.1:8.2:0.4:0.7, stir, coat it on an aluminum foil, and after air drying, obtain the rare earth sulfide energy-saving material La2S3@Ti 0.99 W 0.01 O2:0.2C 17 H 36 :P(VDF-HFP).
[0045] Example 3
[0046] In the embodiment of the present invention, a rare earth sulfide energy-saving material with the chemical composition Ln2S3@A:xB:C is La2S3@V 0.99 W 0.01 O2:0.2C 16 H 34: P(VDF-HFP);; The preparation method is as follows:
[0047] S1. Weigh lanthanum carbonate and sulfur accurately according to the molar ratio of each element in the chemical formula La2S3, put them into a jar mill, set the rotation speed at 1000 r / min, and grind them for 2 h to obtain a first mixture for standby;
[0048] S2. After taking out sulfur according to the molar ratio of 2:1, put the sulfur into a jar mill, set the rotation speed at 1000 r / min, grind it for 2 h, and then add activated carbon particles to obtain a second mixture for standby;
[0049] S3. After taking out the first mixture and the second mixture according to the mass ratio of 1.25:1, wrap the first mixture in the second mixture in a cylindrical crucible, and put it into a sintering furnace. Sinter it at 950 °C for 3 h in an air atmosphere. After cooling to room temperature, take it out, remove the wrapping layer, and then grind the sintered product to obtain a third mixture La2S3; The thermal stability of La2S3 is measured to be 400 °C, and its diffuse reflection in the infrared light band reaches 86%, and the yellowness value reaches 68.00;
[0050] S4. Take out vanadium dioxide and ammonium tungstate solution according to the molar ratio of 99:0.143, dissolve vanadium dioxide in an ethanol solvent, stir and add ammonium tungstate solution and 1 wt% polyvinyl alcohol, adjust the pH to 3 - 5 to form a sol, and obtain a core-shell material A after calcination;
[0051] S5. Take out La2S3, polyvinylpyrrolidone and ammonia water according to the mass ratio of 2:0.02:2, add an appropriate amount of ethanol, set the rotation speed at 500 r / min and stir for 3 h, and add the core-shell material A. Wash and dry the obtained product to get La2S3@V 0.99 W 0.01 O2 for standby;
[0052] S6. Stir La2S3@V 0.99 W 0.01 O2 with P(VDF-HFP), acetone, C 16 H 34 and water according to the molar ratio of 2:1.1:8.2:0.4:0.7, then coat it on an aluminum foil, and after air drying, obtain a rare earth sulfide energy-saving material La2S3@V 0.99 W 0.01 O2:0.2C 16 H 34 :P(VDF-HFP).
[0053] For La2S3@V 0.99 W 0.01 O2:0.2C 16 H 34: P(VDF-HFP) is coated on the surface of a 20*20*20 cm cube made of wood. At the same time, an uncoated sample is selected for comparison. The two groups of samples are placed at room temperature from 6:00 am to 6:00 pm. Comparing with the uncoated sample, it is found that La2S3@V 0.99 W 0.01 O2:0.2C 16 H 34 : The internal temperature of the wood coated with P(VDF-HFP) is reduced by up to 9.5 °C at most. Comparing the temperature drop curves, it is found that La2S3@V 0.99 W 0.01 O2:0.2C 16 H 34 : The internal temperature of the wood coated with P(VDF-HFP) is increased by 5 °C. The temperature difference is as Figure 3 shown. Its weather resistance grade is 5, the salt spray resistance time is 2033 h, and the light resistance grade is 8.
[0054] Example 4
[0055] In the embodiment of the present invention, a rare earth sulfide energy-saving material with a chemical composition of Ln2S3@A:xB:C is Zn 0.05 La 1.95 S3@Ti 0.99 W 0.01 O2:0.2C 18 H 38 : PU; its preparation method is as follows:
[0056] S1. According to the molar ratio of each element in the chemical formula Zn 0.05 La 1.95 S3, zinc oxide, lanthanum carbonate, and sulfur are accurately weighed. After the three are ground and mixed, they are sintered in solid phase to obtain a first product for standby;
[0057] S2. Tetrabutyl titanate, ammonium tungstate solution, and polyethylene glycol are taken out according to the molar ratio of 99:0.143:0.01. Tetrabutyl titanate is dissolved in an ethanol solvent and stirred and added to the ammonium tungstate solution and polyethylene glycol. The pH is adjusted to 3-5 to form a sol, and a core-shell material A is obtained after calcination;
[0058] S3. The first product, ammonia water, and polyvinylpyrrolidone are taken out according to the ratio of (2-4 g):(2-4 ml):(0.01-0.1 g), dissolved in ethanol, stirred, and slowly added to the core-shell material A. The product is washed and dried to obtain a second product for standby;
[0059] S4. The second product, acetone, C 18 H 38After [substance] and PU are dissolved in water and ultrasonically mixed into a homogeneous solution, the homogeneous solution is slowly introduced into a petri dish and leveled, and then naturally dried at room temperature to obtain the rare earth sulfide energy-saving material Zn 0.05 La 1.95 S3@Ti 0.99 W 0.01 O2:0.2C 18 H 38 :PU.
[0060] Apply Zn 0.05 La 1.95 S3@Ti 0.99 W 0.01 :0.2C 18 H 38 :PU on the surface of a 20*20*20 cm cube made of wood. At the same time, an uncoated sample is selected as a comparison. The two groups of samples are placed at room temperature from 6:00 am to 6:00 pm. Compared with the uncoated sample, it is found that the internal temperature of the wood coated with Zn 0.05 La 1.95 S3@Ti 0.99 W 0.01 O2:0.2C 18 H 38 :PU has decreased by 11°C. The internal temperature of the wood is measured at night from 6:00 pm to 5:00 am the next day. Compared with the uncoated sample, it is found that the internal temperature of the wood coated with Zn 0.05 La 1.95 S3@Ti 0.99 W 0.01 O2:0.2C 18 H 38 :PU has increased by 5.1°C. Its weather resistance level is detected to be 5, the salt spray resistance time is 2040 h, and the light resistance level is 8.
[0061] Example 5
[0062] In the embodiment of the present invention, a rare earth sulfide composite energy-saving material with a chemical composition of Ln2S3@A:xB:C is Na 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3:PC; The preparation method is as follows:
[0063] S1. According to the molar ratio of each element in the chemical formula Na 0.015 La 1.985 S3, accurately weigh sodium carbonate, neodymium carbonate, and sulfur, and then grind and mix the three and sinter them in solid phase to obtain the first product for standby;
[0064] S2. Take out isopropyl titanate, ammonium metatungstate solution and polyvinyl alcohol according to the molar ratio of 99:0.083:0.01. Dissolve isopropyl titanate in an ethanol solvent, stir and add ammonium metatungstate solution and polyvinyl alcohol, adjust the pH to 3-5 to form a sol, and obtain core-shell material A after calcination;
[0065] S3. Take out the first product, ammonia water and polyethylene glycol according to the ratio of (2-4 g):(2-4 ml):(0.01-0.1 g), dissolve them in ethanol, stir and slowly add core-shell material A. Wash and dry the product to obtain the second product for standby;
[0066] S4. Take out the second product, acetone, C3H8O3 and PC according to the mass ratio of (0.3-5):1:(5-7):(5-9), dissolve them in water, ultrasonically mix to form a homogeneous solution, slowly pour the homogeneous solution into a petri dish and perform a leveling operation, and then naturally dry at room temperature to obtain the rare earth sulfide energy-saving material Na 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3:PC.
[0067] Coat Na 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3:PC on the surface of a 20*20*20 cm cube made of wood. At the same time, select an uncoated sample for comparison. Place the two groups of samples at room temperature from 9:00 am to 3:00 pm. Comparing with the uncoated sample, it is found that the internal temperature of the wood coated with Na 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3:PC has decreased by 16 °C. By providing a high-temperature environment, monitor the temperature difference between the inside of the object coated with Na 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3:PC and the inside of the uncoated transparent acrylic box. The results show that: in the high-temperature case, the maximum temperature difference between the uncoated sample and the acrylic box coated with Na 0.015 Nd 1.985 S3@Ti 0.99 W 0.01 O2:0.2C3H8O3:PC is 4.2 °C. The temperature difference is as Figure 4 shown. Detect its weather resistance level as 5, the salt spray resistance time is 2039 h, and the light resistance level is 8.
[0068] Example 6
[0069] In an embodiment of the present invention, a rare earth sulfide composite energy-saving material has a chemical composition of Ln2S3@A:xB:C, where C is Ba 0.012 Sm 1.988 S3@Ti 0.95 W 0.05 O2:0.2CH3(CH2)6COOH:PP; The preparation method is as follows:
[0070] S1. According to the molar ratio of each element in the chemical formula Ba 0.012 Sm 1.988 S3, accurately weigh barium carbonate, samarium oxide, and sulfur, and after grinding and mixing the three, perform solid-phase sintering to obtain a first product for standby;
[0071] S2. Take titanium tetrachloride and ammonium tungstate solutions according to a molar ratio of 95:0.714. Dissolve tetrabutyl titanate in an ethanol solvent, stir and add it to the ammonium tungstate solution and 1 wt% polyvinyl alcohol, adjust the pH to 3 - 5 to form a sol, and obtain a core-shell material A after calcination;
[0072] S3. Take the first product, ammonia water, and polyoxyethylene ether according to a ratio of (2 - 4 g):(2 - 4 ml):(0.01 - 0.1 g), dissolve them in ethanol, stir, and slowly add the core-shell material A. Wash and dry the product to obtain a second product for standby;
[0073] S4. Take the second product, isopropanol, CH3(CH2)6COOH, and PP according to a mass ratio of (0.3 - 5):1:(5 - 7):(5 - 9), dissolve them in water, ultrasonically mix to form a homogeneous solution, slowly pour the homogeneous solution into a petri dish and perform a leveling operation, and then coat it on an aluminum foil and naturally dry it at room temperature to obtain the rare earth sulfide energy-saving material Ba 0.012 Sm 1.988 S3@Ti 0.95 W 0.05 O2:0.2CH3(CH2)6COOH:PP.
[0074] Coat Ba 0.012 Sm 1.988 S3@Ti 0.95 W 0.05 O2:0.2CH3(CH2)6COOH:PP on the surface of a 20*20*20 cm cube made of wood. At the same time, select an uncoated sample for comparison. Place the two groups of samples at room temperature from 9:00 am to 3:00 pm. Comparing with the uncoated sample, it is found that Ba 0.012 Sm 1.988 S3@Ti 0.95 W 0.05The internal temperature of the wood coated with O2:0.2CH3(CH2)6COOH:PP decreased by 5 °C. By providing a low-temperature environment, Ba was monitored. 0.012 Sm 1.988 S3@Ti 0.95 W 0.05 The temperature difference between the inside of the object coated with O2:0.2CH3(CH2)6COOH:PP and the inside of the uncoated transparent acrylic box was measured. The results showed that: at low temperatures, the uncoated sample and Ba 0.012 Sm 1.988 S3@Ti 0.95 W 0.05 Compared with the acrylic box coated with O2:0.2CH3(CH2)6COOH:PP, the energy consumption difference saved was 305 W·m -2 , and the energy consumption difference is as Figure 6 shown. Its weather resistance grade was detected to be 5, the salt spray resistance time was 2055 h, and the light resistance grade was 8.
[0075] Example 7
[0076] In the embodiment of the present invention, a rare earth sulfide composite energy-saving material with the chemical composition Ln2S3@A:xB:C is Sn 0.02 Eu 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)8COOH:P(VDF-HFP); its preparation method is as follows:
[0077] S1. According to the molar ratio of each element in the chemical formula Sn 0.02 Eu 1.98 S3, tin oxide, europium sulfate, and sulfur were accurately weighed, and then the three were ground and mixed and sintered in solid phase to obtain the first product for later use;
[0078] S2. Vanadium dioxide and ammonium tungstate solution were taken out according to the molar ratio of 99:0.143. Vanadium dioxide was dissolved in an ethanol solvent, stirred and added to the ammonium tungstate solution and 1 wt% polyvinyl alcohol, and the pH was adjusted to 3-5 to form a sol, which was calcined to obtain the core-shell material A;
[0079] S3. The first product, ammonia water, and polyoxyethylene ether were taken out according to the ratio of (2-4 g):(2-4 ml):(0.01-0.1 g), dissolved in ethanol, stirred, and slowly added to the core-shell material A. The product was washed and dried to obtain the second product for later use;
[0080] S4. Take out the second product, isopropanol, CH3(CH2)8COOH and P(VDF-HFP) according to the mass ratio of (0.3-5):1:(5-7):(5-9), dissolve them in water and ultrasonically mix to form a homogeneous solution. Slowly introduce the homogeneous solution into a petri dish and perform a leveling operation, and then coat it on aluminum foil and naturally dry it at room temperature to obtain the rare earth sulfide energy-saving material Sn 0.02 Eu 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)8COOH:P(VDF-HFP).
[0081] Coat Sn 0.02 Eu 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)8COOH:P(VDF-HFP) on the surface of a 20*20*20 cm cube made of wood. At the same time, select an uncoated sample as a comparison. Place the two groups of samples at room temperature from 9:00 am to 3:00 pm. Comparing with the uncoated sample, it is found that Sn 0.02 Eu 1.98 S3@V 0.99 W 0.01 The internal temperature of the wood coated with O2:0.2CH3(CH2)8COOH:P(VDF-HFP) decreased by 18 °C. The night temperature was measured from 18:00 to 5:00 the next day. Comparing, it was found that Sn 0.02 Eu 1.98 S3@V 0.99 W 0.01 The internal temperature of the wood coated with O2:0.2CH3(CH2)8COOH:P(VDF-HFP) increased by 5.7 °C. Its weather resistance grade was detected to be 5, the salt spray resistance time was 2038 h, and the light resistance grade was 8.
[0082] Example 8
[0083] In the embodiment of the present invention, a rare earth sulfide composite energy-saving material with the chemical composition Ln2S3@A:xB:C is Al 0.02 Y 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)6COOH:PS; its preparation method is as follows:
[0084] S1. According to the molar ratio of each element in the chemical formula SnLa2S5, accurately weigh aluminum carbonate, yttrium carbonate, and sulfur, grind and mix the three, and then perform solid-phase sintering to obtain the first product for later use;
[0085] S2. Take vanadium dioxide and ammonium tungstate solution according to the molar ratio of 99:0.143. Dissolve vanadium dioxide in an ethanol solvent, stir and add ammonium tungstate solution and 1 wt% polyvinyl alcohol, adjust the pH to 3 - 5 to form a sol, and obtain core-shell material A after calcination;
[0086] S3. Take the first product, ammonia water and polyoxyethylene ether according to the ratio of (2 - 4 g):(2 - 4 ml):(0.01 - 0.1 g), dissolve them in ethanol, stir and slowly add core-shell material A. Wash and dry the product to obtain the second product for standby;
[0087] S4. Take the second product, ethyl acetate, CH3(CH2)6COOH and PS according to the mass ratio of (0.3 - 5):1:(5 - 7):(5 - 9), dissolve them in water, ultrasonically mix to form a homogeneous solution, slowly pour the homogeneous solution into a petri dish and perform a leveling operation, and then coat it on aluminum foil and naturally dry it at room temperature to obtain the rare earth sulfide energy-saving material Al 0.02 Y 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)6COOH:PS.
[0088] Coat Al 0.02 Y 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)6COOH:PS on the surface of a 20*20*20 cm cube made of wood. At the same time, select an uncoated sample as a comparison. Place the two groups of samples at room temperature from 9:00 am to 3:00 pm. Comparing with the uncoated sample, it is found that the internal temperature of the wood coated with Al 0.02 Y 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)6COOH:PS has decreased by 14 °C. Measure the temperature at night from 18:00 to 5:00 the next day. Comparing, it is found that the internal temperature of the wood coated with Al 0.02 Y 1.98 S3@V 0.99 W 0.01 O2:0.2CH3(CH2)6COOH:PS has increased by 5.9 °C. Detect its weather resistance level is 5, the salt spray resistance time is 2042 h, and the light resistance level is 8.
[0089] The above is only the preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and all should be covered within the protection scope of the present invention.
Claims
1. A rare earth sulfide energy-saving material, characterized in that, It is prepared from core-shell material A, functional temperature-regulating material B, load C, and rare-earth sulfide Ln2S3, with a chemical composition of Ln2S3@A:xB:C, where x represents the mass fraction of B, which is any value between 0.1 and 0.3 relative to the mass ratio of the energy-saving material. The preparation method includes the following steps: S1. Grind and uniformly mix a flux, a sulfur source, and a rare-earth-based sulfurization precursor in a predetermined ratio, and then carry out a solid-phase sintering reaction to obtain a first product of rare-earth sulfide; S2. Dissolve a metal precursor in an ethanol solvent, stir and add a tungsten-oxygen precursor solution and a coupling agent with a total molar amount of 1-5%, adjust the pH to 3-5 to form a sol, and obtain core-shell material A after calcination; S3. Dissolve the first product and a surfactant in ethanol, then adjust the pH to 3-5, and slowly add core-shell material A under stirring conditions. Wash and dry the product to obtain a second product; S4. Mix the second product with functional temperature-regulating material B, load C, a dispersant, and water, ultrasonicate, and then pour it into a petri dish to level it, and naturally dry it to obtain a rare-earth sulfide composite energy-saving material.
2. The rare earth sulfide energy-saving material according to claim 1, characterized in that, The core-shell material A is titanium dioxide doped with tungsten or vanadium dioxide.
3. The rare earth sulfide energy-saving material according to claim 1, characterized in that, The flux is one or more of sodium carbonate, sodium chloride, and sodium sulfate.
4. A rare earth sulfide energy-saving material according to claim 1, characterized in that, The sulfur source is one or more of sulfur powder, ammonium thiocyanate, and thiourea.
5. The rare earth sulfide energy-saving material according to claim 1, characterized in that, The rare-earth-based sulfurization precursor is a mixture of an Ln compound and a doping element compound, and the molar ratio of Ln to the doping element is (1-0.95):(0-0.05), where Ln is one of lanthanum, yttrium, samarium, neodymium, cerium, and europium, and the doping element is one of gallium, zinc, aluminum, sodium, barium, and tin.
6. The rare earth sulfide energy-saving material according to claim 1, characterized in that The metal precursor is one or more of tetrabutyl titanate, isopropyl titanate, titanium tetrachloride, and vanadium dioxide.
7. The rare earth sulfide energy-saving material according to claim 1, characterized in that, The tungsten-oxygen precursor is one or more of ammonium tungstate, ammonium metatungstate, and tungsten trioxide.
8. The rare earth sulfide energy-saving material according to claim 1, characterized in that, The coupling agent is one or more of polyvinyl alcohol, polyethylene glycol, and γ-(methacryloyloxy)propyltrimethoxysilane.
9. A rare earth sulfide energy-saving material according to claim 1, characterized in that, The surfactant is one or more of polyvinylpyrrolidone, polyoxyethylene ether, polyethylene glycol, and alkylphenol polyoxyethylene ether.
10. The rare earth sulfide energy-saving material according to claim 1, wherein The functional temperature-regulating material B is one or more of hexadecane, heptadecane, octadecane, glycerol, octanoic acid, and decanoic acid.
11. A rare earth sulfide energy-saving material according to claim 1, characterized in that, The load C is one of polypropylene, polystyrene, polyurethane, polymethyl methacrylate, polycarbonate, and polyvinylidene fluoride-hexafluoropropylene.
12. A rare earth sulfide energy-saving material according to claim 1, characterized in that, The dispersant is one or more of acetone, isopropyl alcohol, and ethyl acetate.
13. The preparation method of a rare earth sulfide energy-saving material according to claim 1, characterized in that, In the S1 step, the sintering furnace is one of a box furnace, a tube furnace, and a lifting furnace, the sintering temperature is 800-1000 °C, the sintering time is 1-8 h, and the sintering atmosphere is an air atmosphere.
14. The preparation method of a rare earth sulfide energy-saving material according to claim 1, characterized in that, In the S1 step, the grinding and mixing is one of ball milling, air milling, and water milling; among them, the ball milling rate is 80-900 r / min, and the ball milling time is 1-4 h; the air milling rate is 70-800 r / min, and the ball milling time is 1-4 h; the water milling rate is 80-950 r / min, and the water milling time is 1-4 h.
15. The preparation method of a rare earth sulfide energy-saving material according to claim 1, characterized in that, In the S2 step, the stirring rate is 300-600 r / min, and the stirring time is 3-6 h.